THE USE OF FLASHCARD IN IMPROVING THE LEARNERS' ENGLISH SKILL AT RUMAH BAHASA - Rismawati Wardani; Fatimah Hidayahni Amin; Seny Luhriyani (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
This study aims to measure the extent to which the use of flashcards can be utilized to improve learners' English language skills at Rumah Bahasa. The subjects of the study were 4-5 years old children in Rumah Bahasa Makassar class with a total of 3 children and 3 teachers. This research uses qualitative data to describe the improvement of English learning using flashcards, this is evidenced by learners being able to master English vocabulary and improve development in describing pictures with simple English, responding quickly, and easily understanding learning materials using flashcards. Based on the analysis of the difficulties faced by the learners, it can be concluded that the difficulties faced by the learners are difficulties in pronouncing English words with fluent and correct pronunciation, memorizing vocabulary that has many syllables, and boredom are the difficulties experienced by the learners